Investigating students’ satisfaction level on implicit services of Malaysian public higher education institutions / Wan Nurashikin Mahmood, Mohamad Ridhuan Mat Dangi and Khairul Anuar Mohd Ali - Mahmood, Wan Nurashikin; Mat Dangi, Mohamad Ridhuan; Mohd Ali, Khairul Anuar (Universiti Teknologi MARA Cawangan Pahang, 2014)
This paper attempts to assess the factors that influence the students‟ satisfaction level towards higher learning education system. By adopting simple random sampling technique, this study was participated by 401 respondents from a university in the East Coast region of Malaysia. This study emphasizes on the implicit services provided by the university which include admission and registration; the student affairs services; and teaching, learning and assessment. The findings indicated that majority of the respondents were satisfied with the teaching, learning and assessment aspects. Nevertheless, some factors need more attention and improvement as they indicate a lower level of satisfaction.